2021
DOI: 10.3390/pharmaceutics13020234
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Responsive PLGA-PEG-PLGA Hydrogels as Novel Injectable Platforms for Neuroprotective Combined Therapies in the Treatment of Retinal Degenerative Diseases

Abstract: The present study aims to develop a thermo-responsive-injectable hydrogel (HyG) based on PLGA-PEG-PLGA (PLGA = poly-(DL-lactic acid co-glycolic acid); PEG = polyethylene glycol) to deliver neuroprotective agents to the retina over time. Two PLGA-PEG PLGA copolymers with different PEG:LA:GA ratios (1:1.54:23.1 and 1:2.25:22.5) for HyG-1 and HyG-2 development respectively were synthetized and characterized by different techniques (gel permeation chromatography (GPC), nuclear magnetic resonance (NMR), dynamic lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 61 publications
(87 reference statements)
0
25
0
Order By: Relevance
“…7 of Lopez-cano et al's paper are modeled using this method and force field. This article, which is an MDPI article 38 , deals with the treatment of retinal degenerative diseases with the help of PLGA-PEG-PLGA hydrogel. In Fig.…”
Section: Methodsmentioning
confidence: 99%
“…7 of Lopez-cano et al's paper are modeled using this method and force field. This article, which is an MDPI article 38 , deals with the treatment of retinal degenerative diseases with the help of PLGA-PEG-PLGA hydrogel. In Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The method is simple and the raw materials are easily available. The particle size of the microspheres and the drug loading rate showed good results (21). Studies showed that the stronger the drug was when the nanoparticle size was at the level of 50-100nm (22)(23).…”
Section: Comparison Of Clinical Effectsmentioning
confidence: 99%
“…Combining PLGA-PEG-PLGA to Avastin ® shifted sol-gel transition to low temperature. These are used for treating posterior segment disease of the eyes [ 270 , 271 ].…”
Section: Patent and Current Clinical Trial Status Of The Hydrogel Dru...mentioning
confidence: 99%